Phosphorus and Aluminum Interactions in Soybean in Relation to Aluminum Tolerance. Exudation of Specific Organic Acids from Different Regions of the Intact Root System - Liao, Hong (American Society of Plant Biologists, 2006)
Aluminum (Al) toxicity and phosphorus (P) deficiency often coexist in acid soils that severely limit crop growth and production, including soybean (Glycine max). Understanding the physiological mechanisms relating to plant Al and P interactions should help facilitate the development of more Al-tolerant and/or P-efficient crops. In this study, both homogeneous and heterogeneous nutrient solution experiments were conducted to study the effects of Al and P interactions on soybean root growth and root organic acid exudation. In the homogenous solution experiments with a uniform Al and P distribution in the bulk solution, P addition significantly increased Al tolerance in four soybean genotypes differing in P efficiency. The two P-efficient genotypes appeared to be more Al tolerant than the two P-inefficient genotypes under these high-P conditions. Analysis of root exudates indicated Al toxicity induced citrate exudation, P deficiency triggered oxalate exudation, and malate release was induced by both treatments. To more closely mimic low-P acid soils where P deficiency and Al toxicity are often much greater in the lower soil horizons, a divided root chamber/nutrient solution approach was employed to impose elevated P conditions in the simulated upper soil horizon, and Al toxicity/P deficiency in the lower horizon. Under these conditions, we found that the two P-efficient genotypes were more Al tolerant during the early stages of the experiment than the P-inefficient lines. Although the same three organic acids were exuded by roots in the divided chamber experiments, their exudation patterns were different from those in the homogeneous solution system. The two P-efficient genotypes secreted more malate from the taproot tip, suggesting that improved P nutrition may enhance exudation of organic acids in the root regions dealing with the greatest Al toxicity, thus enhancing Al tolerance. These findings demonstrate that P efficiency may play a role in Al tolerance in soybean. Phosphorus-efficient genotypes may be able to enhance Al tolerance not only through direct Al-P interactions but also through indirect interactions associated with stimulated exudation of different Al-chelating organic acids in specific roots and root regions.